وظيفة البنى اللغوية في تشكيل رؤية الشاعر أدونيس للعالم – ديوان الحصار – نموذجاً (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2019)
The Function of Linguistic Structures in Shaping Adonis's Vision of the World: The Siege as an Applied Model We chose the poet Adonis for a reason: he is a problematic poet, critic and thinker, who came out of the "heart of heritage" and from among the mainstays of modernity. It is not possible to study all of his work in one project. Therefore, his book The Siege, as he calls it, appears as a landmark in which he intensifies many forms of structures: the lexicon, syntactic, morphological, grammatical and symbolical structures, which all seem to interconnect amongst each other. We have overlooked the musical structure for it seems a bit not connected to our study. We have studied the question of interpretation and understanding through the constitutive relations of the semantic structures, and the cultural structure has been looked at in each of these structures, in which Adonis appeared as a critic of heritage and a historian of modernity and of new language. Indeed Adonis showed a unique proficiency in language skills: letters, vocabulary and beautiful patterns. He was also very skillful in their investment, and he harnessed all the diverging forms in the ways he sees the world emanating from the heritage and its infusion into the present and its problems. We have also been aware of the ways in which Adonis employed metaphor and symbol to revolutionize the fossilized stereotype, for the deep-rooted metaphor has its own distinguished and effective way of achieving its project.
Keywords: The modernist implication; Conceptual blogs; Rhetorical performance; Linguistic architecture